Perancangan dan Implementasi Sistem Informasi Kumpulan Resep Masakan Berbasis Web Menggunakan Metode Waterfall - Nabilah Azizi, Jovita; Damara, Rafli; Olivia Silalahi, Ester; Farhan Fahrezy, Muhammad; Nasir, Muhammad; Wicaksono, Aditya (Jurnal ICT: Information Communication & Technology, 2025)
Web-based information systems have become a popular solution for distributing information quickly, efficiently, and accessible to a wide range of users. In the context of recipe management, this system is designed to facilitate users in storing, searching, and sharing recipes in a practical and structured manner. The main goal of developing this system is to provide a digital platform that supports daily cooking activities by presenting complete and easily accessible recipe information. The development method used is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The system developed is an interactive website featuring recipe search by name or ingredient, recipe categorization, recipe uploads by users, and account management. Testing was conducted using the black box method to ensure that each feature functions according to its specifications. The test results show that all system components run well, are responsive, and meet user needs. This system is expected to help users find cooking inspiration, organize recipe collections, and share recipes within a user-friendly and easily accessible digital community.